Adsorption-desorption of anthocyanins from jambolan (Syzygium cumini) fruit in laponite® platelets: Kinetic models, physicochemical characterization, and functional properties of biohybrids. (February 2021) - Coelho Leandro, Gabriel; Capello, Cristiane; Luiza Koop, Betina; Garcez, Jussara; Rodrigues Monteiro, Alcilene; Ayala Valencia, Germán
Graphical abstract: Highlights: Laponite® can adsorb until 93% of anthocyanins from jambolan fruit extract. Freundlich and pseudo-first-order kinetic models described adequately the adsorption process. Anthocyanin-laponite® powder can be used as a colorimetric indicator material at pH ≥ 7. Anthocyanin-laponite® powder has antioxidant properties. Abstract: This study aims to develop and characterize biohybrids (BH) based on anthocyanins (ACNs) from jambolan ( Syzygium cumini ) and laponite® (Lap). ACNs from jambolan fruit were extracted using an acidified water solution at pH 1. ACNs were recovered from extract using Lap as adsorbent between 5 °C and 40 °C. There was no significant effect ( p > 0.05) of the temperature on the adsorption process of ACNs. Thus, the process was classified as physical adsorption in heterogeneous sites where ACNs were stabilized by means of van der Waals force, π − π force, and hydrogen bonding on the Lap surface. After adsorption, the BH powder appeared to have an amorphous structure and red color. However, the color changed at pH ≥ 7. In addition, the obtained BH showed antioxidant properties and high stability when exposed to visible light irradiation. This research reports new information about the valorization and application of ACNs from jambolan for food industrial applications.